Implementation of Islamic Education Concept in Ethnochemistry - Wahyudiati, Dwi (Universitas Muhammadiyah Magelang, 2022)
The concept of Islamic education requires more than just a theoretical understanding. It concentrates only on Islamic studies because of the difficulties in using a chemical perspective to understand the concepts. Therefore, this study aims to implement an Islamic education concept in ethnochemistry using Sasak traditional wisdom. It uses qualitative methodologies such as observation, in-depth interviews, documentation, and curriculum analysis to obtain data. The results show that ethnochemistry based on the local wisdom of the Sasak tribe has a strong relationship with the Islamic education concept, especially in the merarik (marriage) ceremony. A fundamental part of Islamic education is a belief in the need for mutual respect, cooperation, open debate, and consensus, reciprocal give and take, collaboration, and the necessity for stability. These ideas are also very relevant to the chemical bond theory, which includes concepts such as electron stability, electron configuration, positive and negative ion formation, as well as chemical bond formation. Therefore, ethnochemistry based on Sasak local wisdom can be considered relevant to the Islamic education concept. Acknowledging intellectually and ethically intelligent students is essential to achieving national education goals.